Antioxidant Activity of Baby Java Citrus Peel Extract Promotes Lung Tissue Repair in Mice Challenged by Lipopolysaccharides: Antioxidant Activity of BJE Promotes Lung Tissue Repair - Rachmawati, Farida; Sari, Fikriya Novita; Sakti, Sefihara Paramitha; Sakti, Muhammad Wisam Wira; Rahayu, Sri; Soewondo, Aris; Rifa'i, Muhaimin (Journal of Tropical Life Science, 2024)
Acute lung injury tends to be induced by infection or sepsis that disrupt alveolar and vascular permeability, neutrophil influx, and edema. Those impairments are worsened by the increase of oxidative stress along with hyperinflammation response. Oxidative stress in lung tissue could be indicated by malondialdehyde (MDA) and nuclear factor erythroid 2-related factor 2 (Nrf2) expression. This research aimed to evaluate the efficacy of Baby Java citrus peel extract (BJE) in suppressing oxidative stress and preventing lung injury in lipopolysaccharides (LPS)-induced mice. Twenty-five male BALB/c mice were divided into five groups consisting of untreated (N), LPS (A), and LPS-induced followed by treatment using BJE at various doses: 75 mg/kg BW (BJE-1), 105 mg/kg BW (BJE-2), and 150 mg/kg BW (BJE-3). Lungs were isolated for histopathological analysis also detection of MDA and Nrf2 using flow cytometry. BJE at the dose of 105 mg/kg BW could inhibit the alteration of lung histology following LPS challenge including alveolar and interstitial neutrophil infiltration, proteinaceous debris, and septal thickening. The same dose also showed good potency in suppressing MDA and Nrf2 levels as oxidative stress indicators. Our findings demonstrated protective effects of Baby Java citrus peel in acute lung injury and oxidative stress prevention after LPS exposure.